Improved discrimination of phenylalanine enantiomers by surface enhanced Raman scattering assay: molecular insight into chiral interaction. Issue 8 (21st March 2022) - He, Yanxiu; Zhou, Qinghai; Wang, Ning; Yang, Haifeng; Liu, Xinling
Abstract : Chiral interaction-based SERS discrimination of phenylalanine (Phe) enantiomers, with the Raman scattering enhancement degree of d -Phe being 50-fold greater than that of l -Phe. Abstract : SERS spectroscopy, a nontraditional chiral analysis tool, is used to discriminate between d - and l -phenylalanine (Phe), with the Raman scattering enhancement degree of d -Phe being 50-fold greater than that of l -Phe. Such discrimination is achieved by chiral interactions between Phe and the chiral drug molecule of sertraline on silver coated gold nanorods.